2021
DOI: 10.1002/jnr.24851
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between white matter microstructure, cardiovascular fitness, gross motor skills, and neurocognitive functioning in children

Abstract: Recent evidence indicates that both cardiovascular fitness and gross motor skill performance are related to enhanced neurocognitive functioning in children by influencing brain structure and functioning. This study investigates the role of white matter microstructure in the relationship of both cardiovascular fitness and gross motor skills with neurocognitive functioning in healthy children. In total 92 children (mean age 9.1 years, range 8.0–10.7) were included in this study. Cardiovascular fitness and gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
(137 reference statements)
1
11
0
Order By: Relevance
“…Our findings expand these findings and indicate a mediating role of RSNs for both cardiovascular fitness and gross motor skills with neurocognitive functioning in healthy children. Interestingly, in previous work, we also found associations between both cardiovascular fitness and gross motor skills with white matter microstructure that related to the same neurocognitive functions as the current study (Information Processing and Control; Meijer et al, 2021). Together, these findings suggest that both structural and functional aspects of brain networks may respond to physical activity through effects on cardiovascular fitness or gross motor skills.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings expand these findings and indicate a mediating role of RSNs for both cardiovascular fitness and gross motor skills with neurocognitive functioning in healthy children. Interestingly, in previous work, we also found associations between both cardiovascular fitness and gross motor skills with white matter microstructure that related to the same neurocognitive functions as the current study (Information Processing and Control; Meijer et al, 2021). Together, these findings suggest that both structural and functional aspects of brain networks may respond to physical activity through effects on cardiovascular fitness or gross motor skills.…”
Section: Discussionsupporting
confidence: 86%
“…The speculation that coordination and dexterity may be associated with this temporally selective process (i.e., preparatory) was confirmed by the weak to no alpha ERS/ERD during the early stage of stimulus evaluation in the current and previous research 50 . Moreover, parietal upper alpha ERD has been associated with the fronto-parieto-occipital attention system 52 54 , which largely overlaps with the brain structure and connectivity that benefit from MC 59 , 60 as well as the attention networks during early development 2 . Thus, the observed association of coordination and dexterity with upper alpha ERD may be a manifestation of superior functioning of these networks.…”
Section: Discussionmentioning
confidence: 99%
“…Ruotsalainen, et al, (2020) found that in 12-16 years old adolescents the white-matter microstructure of the corpus callosum moderates the association between cardiorespiratory fitness and working memory 75 . Maijer et al, (2021) found no significant mediation of FA in the relationship between cardiorespiratory fitness and neurocognitive functioning 80 . Our finding of a trend for a mediating role of the brain phenotype in the relationship between fitness and cognition builds on this existing literature.…”
Section: Mediation Role Of Brain Microstructurementioning
confidence: 99%